Medical Culture Is An Important Link Of Public Health - Kushmatova Dildora Ergashevna; Olimjonova Farahnoza Orifjonovna (Peerian Journals Publishing, 2024)
This article highlights the issues of raising the solid foundations of the future of medical culture and society, and strengthening both material and spiritual attention to medical science.
Keywords: Medical culture; development of medical science; solid foundation of the future